2017
DOI: 10.1002/ima.22210
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal medical image fusion based on discrete Tchebichef moments and pulse coupled neural network

Abstract: Multimodal medical image fusion plays a vital role in clinical diagnoses and treatment planning. In many image fusion methods-based pulse coupled neural network (PCNN), normalized coefficients are used to motivate the PCNN, and this makes the fused image blur, detail loss, and decreases contrast. Moreover, they are limited in dealing with medical images with different modalities. In this article, we present a new multimodal medical image fusion method based on discrete Tchebichef moments and pulse coupled neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Image fusion is the process of perceptually combining the important features from more than one image into a single image which retains the significant features of both the images. 4 The fusion process can be performed at different levels such as pixel, signal, and feature. The limitations of spatial domain methods are spectral distortion and contrast level reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Image fusion is the process of perceptually combining the important features from more than one image into a single image which retains the significant features of both the images. 4 The fusion process can be performed at different levels such as pixel, signal, and feature. The limitations of spatial domain methods are spectral distortion and contrast level reduction.…”
Section: Introductionmentioning
confidence: 99%
“…There are various medical images such as computed tomography (CT), magnetic resonance imaging (MRI), single photon emission CT (SPECT), and positron emission CT (PET). Single modality medical images may not enough to provide clinical needs to radiologists . Multimodal medical image fusion provides a promising solution approach by integrating information of different modality images into a visual enhanced fused image.…”
Section: Introductionmentioning
confidence: 99%
“…However, its high computational complexity hinders the performance of medical image fusion . Furthermore, it will cause blurring effect at the edge . Recently, researches on brain theory and neuroscience, the Bayesian brain theory, and the free energy (FE) principle reported that the brain works with an internal generative mechanism (IGM) for visual perception and understanding.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations